2020
DOI: 10.4269/ajtmh.20-0299
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Plasmodium falciparum Malaria and Risk Factors for Severe Disease in Hubei Province, China

Abstract: This study aimed to describe the epidemiology of Plasmodium falciparum malaria and identify risk factors for severe disease in Hubei Province, China, using a case-based survey of retrospective data from 2013 to 2018. From 2013 to 2018, a total of 763 imported malaria cases were reported in Hubei Province; 69.2% (528/763) cases were caused by P. falciparum species. The proportion of malaria caused by P. falciparum increased from 66.7% in 2013 to 74.0% in 2018 (χ 2 = 21.378, P < 0.05). Plasmodium falciparum mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…A similar study conducted in Sweden revealed that the percentages of severe imported malaria cases by species were 9.4% due to P. falciparum, 7.7% P. vivax, 5.3% P. ovale, 3.3% P. malariae, and 21.1% mixed infection with P. falciparum [56]. Additionally, the percentages of severe imported falciparum malaria reported in China and Japan were 9.7% and 13.3% respectively [57,58]. In contrast, we reported a higher percentage of severe falciparum malaria patients (36.9%), which was similar to those previously documented in East London, United Kingdom, where 36.3% of falciparum malaria cases were severe [59].…”
Section: Discussionmentioning
confidence: 77%
“…A similar study conducted in Sweden revealed that the percentages of severe imported malaria cases by species were 9.4% due to P. falciparum, 7.7% P. vivax, 5.3% P. ovale, 3.3% P. malariae, and 21.1% mixed infection with P. falciparum [56]. Additionally, the percentages of severe imported falciparum malaria reported in China and Japan were 9.7% and 13.3% respectively [57,58]. In contrast, we reported a higher percentage of severe falciparum malaria patients (36.9%), which was similar to those previously documented in East London, United Kingdom, where 36.3% of falciparum malaria cases were severe [59].…”
Section: Discussionmentioning
confidence: 77%
“…It is however also possible that there may be a reduction in the capacity of the ageing immune system to mount a robust defence against the infection. 11 , 34 Elderly patients are more susceptible to having complications from various infectious diseases. This tends to be a result of multimorbidity and a diminished capacity to establish sufficient immune response.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 This state of diminishing age-specific immunity to malaria has however not been conclusively proven in older individuals in highly endemic areas, who are regularly exposed to plasmodia. 11 , 34 , 37 This is indeed an area for further research, considering that the primary mechanisms of the host response and immunity to plasmodial infection are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies that addressed the risk factors of SM listed some frequently identified factors as distance to the nearest health facility, concurrent comorbidities, nonuse of preventive methods, immune status, pregnancy, duration of illness before receiving antimalarial drug, delayed care, seeking self-medication, and patients' age [ 21–28 ]. For instance, Xia and colleagues have recently found that the risk of SM was higher in females and patients' aged ≥50 years old in the Hubei Province, a low malaria endemic area in China [ 28 ]. Few unusually addressed risk factors such as ethnicity have also been identified among Pf -infected adults [ 29 ].…”
Section: Severe Malariamentioning
confidence: 99%